Miracema do Tocantins: uma cidade em (des)construção - Miranda, Ricardo Ferreira (Universidade Federal do Tocantins, 2016)
This study aims, understand the transformations and urban settings in the city of Miracema do Tocantins, from the development of capitalism in the city before and after his state capital condition, taking as time cutting the 1970s to the present time. The research that has developed is qualitative, the literature review is based on authors such as Santos (1979, 2001, 2003, 2005, 2006), Sposito (2007, 2009), Carlos (1991, 1996) in discussions of urbanization and production of urban space. For the analysis of issues such as public policy and Tocantins territorial occupation we have used the works of several authors such as Oliveira (1991), Ram (1988), Becker (1978), Apollinaire (2006). In addition to the bibliographic analysis research has also been developed through interviews and document analysis.We already have some results about some public policies, such as the deployment of BR153 and SPVEA that hit the city of Miracema do Tocantins, and reconfigured and produced the urban space of the city.but also in relation to the production and reproduction of geographical space process in the city of Tocantins Miracema and the actions of the agents responsible for the production process and reproduction of capital and the urban space in Miracema do Tocantins.